Students 'conceptions about the importance of physics discipline for their professional training as an agricultural technician (Research, Society and Development, 2020)
The present investigation identified the conceptions of Integrated High School students about their performance in the subject of Physics and how they understand the relationship between this subject and the Technical Course in Agricultural and High School at the Federal Institute of Pernambuco (IFPE) - Campus Barreiros. The investigation has a qualitative approach and had the participation of students from the 2nd and 3rd year of high school. A diagnostic questionnaire with three essay questions was applied to these students, in order to answer the central objective of this investigation. The method of analysis for this investigation was Bardin's Content Analysis (2016). The results indicate that more than 80% of the interviewees are unable to identify the relationships that exist between the physical contents learned in basic training with those associated with technical training. Through the results, we understand that the curriculum of the Technical Course in Agriculture is rethought in order to promote a dialogue between the disciplines. It is of fundamental importance that what students learn in basic training also makes sense in technical training.